(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
On August 29, 2023, at Yerevan State University, in off-line and online format, an international scientific and practical conference was held on the topic "Problems and prospects for the development of the environment, hydrometeorology in semi-mountainous and mountainous countries". The purpose of the conference was to discuss, highlight and clarify the main problems, patterns of development and prospects in the field of hydrometeorology, to assess its role in solving the socio-economic problems of the region. The conference was held within the framework of the scientific project of the Scientific Committee of the Ministry of Education, Science, Culture and Sports of the Republic of Armenia (MоESCS) "Water-ecological assessment of the characteristics of the flow of rivers flowing into Lake Sevan during winter low water" carried out by "Armhydromet" of the Ministry of Environment and joint project “Short-term probabilistic forecast of river flow during spring floods” within the framework of the international competition Scientific Committee of the RA MoESCS and the Russian Foundation for Basic Research to support joint scientific research programs. The conference was organized jointly with the Faculty of Geography and Geology of Yerevan State University, St. Petersburg Hydrometeorological University, Faculty of Geography of Moscow State University, All-Russian Research Institute of Civil Defense and Emergency Situations (Federal Center for Science and High Technologies) of the Ministry of Emergency Situations of the Russian Federation. During the conference, many reports were presented on current problems of hydrometeorology and ways to solve them. The speeches were given by: H. Hovhanesyan – Rector of Yerevan State University, L. Azizyan – Director of the SNCO "Armhydromet", E. Gajdukova – Associate Professor of the Department of Engineering Hydrology of the Russian State University of Hydrometeorology (RSUH), M. Bedilo – Director of the All-Russian Research Institute of Civil Defense and Emergency Situations of the Ministry of Emergency Situations of the Russian Federation (Federal Center of Science and High Technologies), Sh. Khachatryan – acting dean of the Faculty of Geography and Geology of the YSU. Levon Azizyan, director of the SNCO "Armhydromet", expressed special gratitude to the RSUH, represented by E. Gaidukova, and the MSU named after M.V. Lomonosov, represented by N. Frolova (scientific director of the project) for their contribution to organize the conference, participation, support and cooperation in the implementation of scientific topics, as well as other organizations supporting the conference, including YSU represented by the rector H. Hovhanesyan and the acting dean of the Faculty of Geography and Geology Sh. Khachatryan for overall support. The conference was attended by representatives of the Russian State University of Hydrometeorology, Belarusian State University, National University named after. V. Karazin of Kharkov, MSU named after M.V. Lomonosov, Gorno-Altai State University, Yugra State University, SNCO “Armhydromet”, Brest State Technical University, All-Russian Research Institute of Civil Defense and Emergency Situations of the Ministry of Emergency Situations of Russia, Tomsk National Research State University, Yerevan State University, National Polytechnic University of Armenia, Institute of Geological Sciences of the NAS RF, Center for Ecological and Noosphere Research, Scientific Center for Zoology and Hydroecology, Institute of Geological Sciences of the NAS RA, Yerevan State Pedagogical University named after Kh. Abovyan, German Organization for International Cooperation, UN Development Programme, Environmental Protection Department of Yerevan municipality, Cadastre Committee. All participants were awarded certificates.